Literackie narracje o kolekcjach - Skorupa, Ewa (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
The article concerns collections and collecting as a literary theme. Research on this issue should be undertaken by literary scholars, as collections support the characteristics of literary characters and give heroes their identity. The work analyzed from this angle is “Money” by Andrzej Strug from the year 1914. It interprets and describes three different collections and three different collectors: the eccentric Lyttons and their museum of stones, Lucy Slazenger’s precious jewelry collection and the art collection of Osias Murwaya, an enthusiast of antiquity.
Literary Narratives on Collections
Keywords: Andrzej Strug; loneliness; collecting; domination; power; museum of stones; tragedy; melancholy; a collection of jewelry; artwork; suicide; samotność; kolekcjonerstwo; dominacja; władza; muzeum kamieni; tragizm; melancholia; kolekcja biżuterii; dzieło sztuki; samobójstwo